Molecular Detection and Antibiotic Resistance of Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio alginolyticus from Shrimp (Penaeus monodon) and Shrimp Environments in Bangladesh. (18th February 2023) - Haque, Zobayda Farzana; Islam, Md. Saiful; Sabuj, Abdullah Al Momen; Pondit, Amrita; Sarkar, Aksya Kumar; Hossain, Md. Golzar; Saha, Sukumar
Abstract : Some Vibrio species can cause food-borne diseases in humans, including cholera, vomiting, septicemia, and gastroenteritis, which are associated with the consumption of contaminated seafood products. The study was conducted to detect antimicrobial-resistant Vibrio species in shrimp and shrimp environments in Bangladesh. Samples of shrimp ( n = 50), water ( n = 50), and mud ( n = 50) were collected aseptically from 50 different shrimp culture ponds in the Khulna region of Bangladesh. Identification of Vibrio species was based on cultural and staining characteristics, biochemical tests, and polymerase chain reaction (PCR). Antimicrobial resistance profiles were determined using a disk diffusion assay. By PCR, Vibrio isolates were found in 34% (95% CI: 26.9%–41.9%) of the samples, of which the detection rate was significantly higher in shrimp (54%), compared to mud (26%) and water (22%). Moreover, V . cholerae, V . parahaemolyticus, and V . alginolyticus were detected in 24.7%, 15.3%, and 4% of the samples, respectively. Among them, the detection rate of V . cholerae and V . alginolyticus was significantly higher in shrimp samples than in other samples. V . parahaemolyticus was also higher in the shrimp samples, but the difference was not statistically significant. Vibrio isolates showed high to moderate resistance (92.2%–15.7%) to ampicillin, amikacin, cefotaxime, tetracycline, ceftazidime, gentamicin, nalidixic acid, levofloxacin, and ciprofloxacin, and low resistance (3.9%) to imipenem, meropenem, chloramphenicol, and trimethoprim-sulfamethoxazole. Interestingly, 52.9% of the isolates were multidrug resistant, and the multiple antibiotic resistance index was up to 1.0. To our knowledge, this is the first study in Bangladesh detecting these three Vibrio species ( V . parahaemolyticus, V . alginolyticus, and V . cholerae ) from shrimp and shrimp environments by molecular approach in the same study. These findings reveal the alarmingly high occurrence of antimicrobial-resistant Vibrio species in shrimp and shrimp environments, which should be of concern to both the shrimp industry and public health management.